INFLUENCES OF TELEVISION TOWARD MODERN SOCIETY REFLECTED IN TV PEOPLE BY HARUKI MURAKAMI - KHIKMAH, ZIYAADATUL (Jurnal Ilmiah Mahasiswa FIB, 2014)
Khikmah, Ziyaadatul. 2014. Influences of Television toward Modern SocietyReflected in TV People By Haruki Murakami. Study Program of English,Department of Languages and Literature, Faculty of Cultural Studies, UniversitasBrawijaya. Supervisor:  Juliati; Co-supervisor : Arcci Tusita. Keyword: Television, Mass Media, Effect, Construction, Culture, Influence. Television has become part of daily life in the society in modern era. Television functions as a medium of information and entertainment. Television becomes interesting with the programs that are presented. However, the function of television is not always positive, it can also give negative impact to viewer because what are presented indirectly can give negative effects to viewers. Thisphenomenon is reflected in a short story TV People which tells about the influence of television in the late 20th Century on the main character’s daily life. Based on this background, the problem of this study is how the main character deals with set of televisions that have influenced his life. Therefore, the writer uses the theory of Television Culture as the main basis for examining the phenomenon of the story to reveal anything shown on television is planned. In addition, this study also applies the theory of the effects of mass media to explain the negative impacts.  Applying cultural approach, the writer reveals three impacts of television on society’s life. First, television influenced one’s habit. The main character in TVPeople his habits for instance watches television so many hours in a day, hishobby of reading has lost. Second, television influenced family interaction because character ‘I’ as a viewer was accustomed to watch TV alone at home. Asa result, he is accustomed to be passive and cannot establish conversation with his wife. Over the time, the conversation between them became lost and he believedon television that his wife had gone away. Third, television influenced the maincharacter’s dream. All of activities of television which are seen, those come intothe dream world of character ‘I’. The writer suggests for the students who intend to conduct a research on thesame short story, to use different perspectives such on semiotics or psychologicalone.